Ascension - Gibson, S. T. (Gibson, S. T. Summoner's circle, 2025)
"As the youngest-ever High Priest of his secret Boston Society, husband to brilliant Moira, and boyfriend to influential psychic David, Rhys McGowan has it all. Now he just has to keep it all whilst trying to save the Society from financial ruin, in-fighting, and sabotage from mysterious outsiders. When leaked documents spark a local Satanic panic and bring the Society under fire, Rhys is willing to gamble everything, even his immortal soul, for more demonic assistance. Growing his retinue of spiritual assistants gives Rhys the magical prowess, charisma, and uncanny luck he needs to captain a sinking ship, but all power comes with a price. Rhys' mind begins to fracture under the strain of juggling so many demons -- and the stress of his loved ones exploring their attraction to other people. As paranoia and rumors spread like wildfire through the occult community, David and Moira will have to once again join forces to pull Rhys back from the brink. But you can't save someone who doesn't want to be saved, and all the magic in the world won't prevent Rhys from having to make the ultimate choice: will he become a great man, or a good one?"-- Provided by publisher.